Quality Analysis Of Liquid Organic Fertilizer Using Raw Vegetable Waste From Pasar Baru Kabupaten Tuban: Analisa Kualitas Pupuk Organik Cair Berbahan Baku Limbah Sayuran Pasar Baru Kabupaten Tuban - Nia Nurfitria; Kuntum Febriyantiningrum; Annisa Rahmawati (Universitas Widya Gama Mahakam, 2020)
This study aims to determine the manufacturing process and the quality of liquid organic fertilizer made from vegetable waste from Pasar Baru, Tuban Regency. Liquid organic fertilizer is done as a solution to the amount of vegetable waste which is the most waste produced by Pasar Baru in Tuban Regency with the amount reaching 2 tons / day. This large amount of vegetable waste will cause environmental problems if not handled and treated properly. The method used in making liquid organic fertilizer is semi anaerobic fermentation using drum composter with the addition of EM-4 bioactivator. The quality of liquid organic fertilizer will be seen based on the physical properties and the results of the analysis of macro nutrient content and adjusted to SNI determined by Permentan No. 70 Th. 2011. The results of the analysis showed that physical properties pH and temperature are fullfill the standard of SNI Permentan No.70 Th. 2011. But for the content of macro elements of C-organic, N, P, and K total are not fullfill the standard.